Functional Interaction of the Ess1 Prolyl Isomerase with Components of the RNA Polymerase II Initiation and Termination Machineries - Krishnamurthy, Shankarling (American Society for Microbiology (ASM), 2009)
The C-terminal domain (CTD) of the largest subunit of RNA polymerase II (Pol II) is a reiterated heptad sequence (Tyr1-Ser2-Pro3-Thr4-Ser5-Pro6-Ser7) that plays a key role in the transcription cycle, coordinating the exchange of transcription and RNA processing factors. The structure of the CTD is flexible and undergoes conformational changes in response to serine phosphorylation and proline isomerization. Here we report that the Ess1 peptidyl prolyl isomerase functionally interacts with the transcription initiation factor TFIIB and with the Ssu72 CTD phosphatase and Pta1 components of the CPF 3′-end processing complex. The ess1(A144T) and ess1(H164R) mutants, initially described by Hanes and coworkers (Yeast 5:55-72, 1989), accumulate the pSer5 phosphorylated form of Pol II; confer phosphate, galactose, and inositol auxotrophies; and fail to activate PHO5, GAL10, and INO1 reporter genes. These mutants are also defective for transcription termination, but in vitro experiments indicate that this defect is not caused by altering the processing efficiency of the cleavage/polyadenylation machinery. Consistent with a role in initiation and termination, Ess1 associates with the promoter and terminator regions of the PMA1 and PHO5 genes. We propose that Ess1 facilitates pSer5-Pro6 dephosphorylation by generating the CTD structural conformation recognized by the Ssu72 phosphatase and that pSer5 dephosphorylation affects both early and late stages of the transcription cycle.